Penetapan Kadar Aspartam Pada Minuman Berenergi “X” Serbuk Dengan Metode Kromatografi Cair Kinerja Tinggi - Abeiasa, M. Saka; Humaira, Vilma; Yuza, Novendra (Universitas Sumatera Barat, 2022)
Energy drinks are currently being consumed by more and more people, which unwittingly contain artificial sweeteners such as aspartame. Aspartame can cause various disorders in the body if consumed in excess of 40 mg/kg body weight. The High Performance Liquid Chromatography (HPLC) method is often used to determine aspartame levels in food or beverages. This study aims to determine the validation of the aspartame aspartame determination method and to determine the aspartame content in energy drink